Construction of Intercultural Dialogue Through Multicultural Education Approach: A Comprehensive Review of Islamic Religious Education Perspective - Ade Hastuty; St. Wardah Hanafie Das (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This review comprehensively examines the construction of intercultural dialogue through a multicultural education approach, focusing on the perspective of Islamic Religious Education (PAI) in Indonesia. In the context of a society rich in cultural, religious, and ethnic diversity, multicultural education becomes an important tool for building understanding, tolerance, and peaceful coexistence. The core principles of multicultural education, such as equality, diversity, intercultural dialogue, social justice, and cultural awareness and sensitivity, are integrated into the PAI curriculum to promote universal Islamic values, such as tasamuh (tolerance) and ukhuwah (brotherhood). The reviewed studies indicate that multicultural education strategies in PAI can enhance attitudes of tolerance and social cohesion among students, creating an inclusive learning environment that values diversity. However, challenges such as limited systemic integration and culturally responsive teacher training remain obstacles. This review recommends strengthening the curriculum, ongoing teacher training, and active community participation to achieve effective and sustainable intercultural dialogue.